1. The problem statement, all variables and given/known data in the third picture , we know that π2 can be written as function of π1 , where π2 is inverse of reynold number , how if i want to change it to π1 = function of π2 , can i write it as (Reynold number ) = F / ρ (D^2)(v^2) ??? p/s : π1 is actually inverse of reynold number 2. Relevant equations 3. The attempt at a solution IMO , for π1 = function of π2 , it is also (Reynold number ) = f (F / ρ (D^2)(v^2) ) ... we should write it as reynold number instead of inverse of reynold number , am i right ?